Factor Influencing to Users’ Acceptance of Digital Payment System - Dadhich, M; Pahwa, M.S; Rao, S.S (International Journal of Computer Sciences and Engineering, 2025)
The worldwide proliferation of internet has propounded the new edge system of electronic payments which is one of the revolutions in economic system. This has replaced the cash economy to plastic card or cloud economy and then transformed to virtual payment system. Today one cannot imagine life without use of internet and mobiles which has virtually kept the banks in the pockets of the general public. The recent demonetization has proved to be a catalyst in increasing the online transactions; thereby the term financial inclusion has gained terrific momentum in recent past. The reforms in information technology along with economic revolution has paved the growth of online payment systems like plastic card, net banking which offer a variety of services to the customers. There have been upward trends in the entire e-payment mode than physical transaction for last two years. This paper studies the issues influencing the acceptance of digital payment system in general. The paper is based on primary sources i.e. questionnaire and data was collected by using judgmental sampling, multiple regression used to conclude the outcome of the data. The findings of the study depicts that four independent variables namely security system, government regulations, convenience, productivity & flexibility were significantly associated with consumer’s intention towards using digital payment mode than technical know-how and internet access. Thus, it can be construed that these variables may pave the way for new age payment system